WEED MANAGEMENT PRACTICES IN TRANSPLANTED KODOMILLET ( ODOMILLET (Paspalum scrobiculatum aspalum scrobiculatum aspalum scrobiculatum L.) - CHANU, YENDREMBAM BEBILA; S. JAWAHAR; K. NANDINI DEVI; Y. SANATOMBI DEVI (The Bioscan, 2018)
A field experiment was carried out at the Experimental Farm,Department of Agronomy, Faculty of Agriculture, Annamalai University, Annamalainagar, Tamil Nadu, India during Kharif season (June-October) 2014 to study the effect of weed management practices in transplanted kodo millet (Paspalum scrobiculatum L.). The experiment consists of six viz., T1 - Unweeded control, T2 - Hand weeding on 20th and 40th days after transplanting (DAT), T3 - Pre – emergence application of Butachlor @1.5 kg a.i /ha on 3 DAT, T4 - Pre - emergence application of Pretilachlor @ 0.5 kg a.i/ ha on 3 DAT, T5 - Post – emergence application of 2, 4, D- Na Salt @ 0.75 kg a.i/ha on 20 DAT and T6 - Post – emergence application of Bispyribac- Sodium @ 20 g /ha on 20 DAT. The experiment was lay out in randomize block design with four replications. The results revealed that hand weeding on 20 and 40 DAT (T2) significantly registered the tallest plant height of 90.32 cm. Highest grain yield of 2884 kg ha-1 was recorded with the hand weeding on 20 and 40 DAT (T2 ). Similarly the highest straw yield (7881.48 kg ha-1) was also observed from hand weeding on 20 and 40 DAT (T2 ). Among the treatments, the highest nutrient uptake N (58.79 kg ha-1), P (19.10 kg ha-1) and K (75.72 kg ha-1) was observed in the hand weeding on 20 and 40 DAT. The maximum available nutrients N (229.02 kg ha-1), P (18.71 kg ha-1) and K (284.35 kg ha-1) were recorded from the treatment of hand weeding on 20 and 40 DAT. The highest B:C ratio (2.41) was recorded from the treatment T6 i.e. post emergence application of bispyribac sodium @ 20 g ha-1 on 20 DAT. Thus, application of bispyribac sodium @ 20 g ha- ¹ on 20 DAT holds immense potentiality to control the all types of weeds, boost the productivity and profitability of transplanted kodo millet.